AUDIT OPINION, FINANCIAL TURBULENCE, AND POLITICAL POWER : WHAT DRIVES AUDITOR SWITCHING? - Icih Icih; Vivian Nurul Insani; Bambang Sugiharto; Fathin Nuril A'isha Binti Mohd Radzi (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2025)
This study aims to examine the effect of audit opinion, audit delay, financial distress, tax aggressiveness, and political connections on auditor switching. The data source used is the annual report of property and real estate companies that have been audited in 2020-2023. This study is a quantitative study with a sampling technique used is purposive sampling with a total sample of 256 data. Data processing uses Microsoft Excel and SPSS version 25. Based on the results of the study using logistic regression, the results of the study show that audit opinion has no effect on auditor switching, audit delay has a positive effect on auditor switching, financial distress has a negative effect on auditor switching, tax aggressiveness has no effect on auditor switching, political connections have a negative effect on auditor switching. Meanwhile, the results of simultaneous testing show that audit opinion, audit delay, financial distress, tax aggressiveness, and political connections simultaneously affect auditor switching. The company size variable acts as a control variable on the effect of audit opinion, audit delay, financial distress, tax aggressiveness, and political connections on auditor switching.